ACCOUNTING PERFORMANCE AS AN ANTECEDENT FACTOR OF CHIEF EXECUTIVE OFFICER TURNOVER IN INDONESIA - Lindrianasari Lindrianasari; Nurdiono Nurdiono; Einde Ivana (Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
This study is aimed to provide empirical evidence about the usefulness of accounting information in the issue of CEO turnover. Previous research shows the results that CEOturnover is inconclusive with respect to its antecedent factors and consequences. It is also very rarely observed in Indonesia, and therefore strongly encourages the author toconduct this study. The samples of this study is all the companies performing turnover (either routine or non-routine) at the level of the company's top leaders in office asPresident Director. The sample included 81 CEOs which experienced turnover from 1998 to 2006 period, and compared with a control group referring to companies that does not perform CEO turnover during the observation period (nine years). The final sample that we used for testing the accounting data is as much as 140 companies, consisting of 81 companies that performed turnover and 59 companies that did not. The results of study show that accounting data (i.e. total assets, total sales, ROA, ROE and earnings), indicates a significant negative effect on turnover decisions, while current ratio does not. In additional tests, we find that the accounting performance on non-routine turnover compares favourably with CEO turnover on the type of routine. This result indicates a bargaining position of CEOs at a company that does change regularly. Meanwhile, worse accounting performance will have the potential for CEOs to be replaced (down position or enter into a council of commissioners) and even be laid off from the company.Keywords: CEO turnover, accounting performance, antecedent factors